Young People and the Shadow of Populism: Reconsidering Democracy and Political Transformation in Indonesia - Hasugian, Alif (Indonesian Journal of Political Studies, 2025)
This paper examines the role of youth within the contemporary political landscape marked by populism. Populism is a form of politics that emphasizes the antagonism between the 'people' versus the 'elite'. As the group most actively supportive of democracy, youth can either reproduce or resist populist narratives. Employing a descriptive qualitative method based on literature review and critical discourse analysis, this study demonstrates that youth play an ambivalent role. On the one hand, populism opens up space for political participation and the expression of generational idealism; on the other hand, it has the potential to deepen identity polarization and weaken the quality of democracy. The author argues that the sustainability of Indonesian democracy is highly dependent on the direction of youth's political idealism whether it is channeled towards an inclusive discourse or becomes trapped in exclusive antagonism.